AMPA receptor positive allosteric modulators attenuate morphine tolerance and dependence. (15th July 2018) - Hu, Xiaoyu; Tian, Xuebi; Guo, Xiao; He, Ying; Chen, Haijun; Zhou, Jia; Wang, Zaijie Jim
Abstract: Development of opioid tolerance and dependence hinders the use of opioids for the treatment of chronic pain. In searching for the mechanism and potential intervention for opioid tolerance and dependence, we studied the action of two positive allosteric modulators of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR PAMs). In mice treated with morphine (100 mg/kg, s.c.), acute morphine tolerance and dependence developed in 4–6 h. Treatment with aniracetam, a well-established AMPAR PAM, was able to completely prevent and reverse the development of acute antinociceptive tolerance to morphine. Partial, but significant, effects of aniracetam on acute morphine induced-physical dependence were also observed. Moreover, aniracetam significantly reversed the established morphine tolerance and dependence in a chronic model of morphine tolerance and dependence produced by intermittent morphine (10 mg/kg, s.c. for 5d). In addition, HJC0122, a new AMPAR PAM was found to have similar effects as aniracetam but with a higher potency. These previously undisclosed actions of AMPAR PAMs are intriguing and may shed lights on understanding the APMA signaling pathway in opioid addiction. Moreover, these data suggest that AMPAR PAMs may have utility in preventing and treating morphine tolerance and dependence. Highlights: Two AMPA receptor positive allosteric modulators aniracetam and HJC0122 were studied. Aniracetam prevented acute morphine tolerance and dependence. Aniracetam and HJC0122 attenuated acute morphine tolerance and dependence. Aniracetam and HJC0122 attenuated chronic morphine tolerance and dependence.